2022
DOI: 10.1002/jgm.3416
|View full text |Cite
|
Sign up to set email alerts
|

ANKRD37 inhibits trophoblast migration and invasion by regulating the NF‐κB pathway in preeclampsia

Abstract: Background Inadequate trophoblast invasion is associated with preeclampsia (PE). Ankyrin repeat domain protein 37 (ANKRD37) has been reported to be abnormally expressed in PE placentas. However, the role of ANKRD37 in trophoblasts has not been investigated. We aimed to determine the functions of ANKRD37 in PE and to explore the molecular mechanisms. Methods Here, fluorescence in situ hybridization, immunohistochemistry, Western blotting and quantitative real‐time polymerase chain reaction were used to detect p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The area under the curve (AUC) values in ROC analysis further support their potential diagnostic efficacy in distinguishing preeclampsia patients from normal controls. Studies have shown that ANKRD37 high expression may inhibit the migration and invasion of trophoblast cells through the NF- κ B pathway, potentially contributing to PE development ( 30 ). In the hypoxic-ischemic environment of preeclampsia, a novel member of the CRH peptide family significantly increases Ucn2 and Ucn3, further promoting the response to oxidative stress in the placenta ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve (AUC) values in ROC analysis further support their potential diagnostic efficacy in distinguishing preeclampsia patients from normal controls. Studies have shown that ANKRD37 high expression may inhibit the migration and invasion of trophoblast cells through the NF- κ B pathway, potentially contributing to PE development ( 30 ). In the hypoxic-ischemic environment of preeclampsia, a novel member of the CRH peptide family significantly increases Ucn2 and Ucn3, further promoting the response to oxidative stress in the placenta ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“… 45 Increased expression of ANKRD37 has been observed in preeclamptic placentas and may inhibit trophoblast cell migration and invasion through the NF‐κB pathway. 46 Researchers propose that ANKRD37 could serve as a novel marker for PE. 47 PFKFB3 , in contrast, is an enzyme involved in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between SLIT3 and villous capillaries will be further confirmed by expanding the sample size in the future, with the aim of providing new biomarkers for predicting abnormalities in villi and villous vascular development. Additionally, although HTR8/SVneo is widely used as a model to study the invasion, migration, metabolism and other functions of placental trophoblast cells ( Basak et al., 2018 ; Tan et al., 2022 ; Yin et al., 2022 ), it cannot fully reflect the real situation of trophoblast cells in vivo due to its own limitations; therefore, primary trophoblast cells should be used to further validated the findings of this study in the future. Furthermore, the specific molecular mechanisms by which miR-491-5p and SLIT3 regulate EP have not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%